(untitled) (International Seven Journal of Multidisciplinary, 2022)
The internationalization of immigrant-led businesses represents a complex and evolving phenomenon at the intersection of global entrepreneurship and strategic management. This paper investigates how Brazilian immigrant entrepreneurs, supported by specialized consultancies like DX Group, are successfully expanding their ventures into international markets despite facing structural and institutional challenges. Using case studies of companies assisted by DX Group, the research highlights how strategic intermediation—through tailored market entry strategies, regulatory compliance, cultural adaptation, and network-based support—enables these businesses to overcome the liability of foreignness and other barriers to international growth. The DX Group’s approach draws on established theoretical frameworks such as the Uppsala model and the resource-based view to develop context-sensitive strategies that align with the capabilities and goals of each client. The paper presents detailed examples of market entry into the United States and the European Union, illustrating how hybrid entry modes and local partnerships can enhance both initial success and long-term sustainability. Ultimately, the study contributes to a deeper understanding of the role of intermediary organizations in facilitating the global expansion of immigrant-owned businesses, offering insights for academics, practitioners, and policymakers interested in inclusive internationalization processes.